Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru PPPK pada UPT SD Negeri 064024, Medan - Masnur Lukito; Budi Hartono; Maksum Syahri Lubis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study was to identify and analyze the Principal's Leadership Role. The factors that inhibit and support the Principal's Leadership Role in Improving PPPK Teacher Performance at UPT SD Negeri 064024. This research is a descriptive type of field research using qualitative methods. Data collection techniques, with Observations, Interviews and Documentation. Steps in analyzing data with Data Reduction, Data Display and Conclusion Drawing/Verification. The results of the study found that the Principal Leadership in the Medan Selayang District was able to establish cooperation, establish communication, build enthusiasm, resolve conflicts, create positive relationships, pay attention to the welfare of teachers. Obstacles to the leadership role of school principals in improving the competence of UPT SD Negeri 064024 Teachers in Medan Selayang District, Medan City, namely: Education and Training, Discipline Level, and Students,